New records of the milliped order Polyzoniida from Korean Peninsula, with a redescription of Kiusiozonium okai (Takakuwa & Miyosi, 1949) (Diplopoda) - Mikhaljova, Elena V.; Lim, Kil-Young (Zootaxa, 2006)
Both the genus Kiusiozonium Verhoeff, 1941 and the species Kiusiozonium okai (Takakuwa & Miyosi, 1949) are recorded in the fauna of Korea for the first time. Angarozonium munsunum Mikhaljova, Golovatch, Wytwer, 2000 is new to the fauna of South Korea. Kiusiozonium okai is redescribed based upon fresh material from South Korea and Japan. Remarks are provided for the two species encountered, including notes on the variation of latter species as well as on the position of the penes in Nearctic and Palaearctic representatives of the family Polyzoniidae.